Maternal age and association with intercorrences in gestation and labor (Research, Society and Development, 2021)
Objective: To analyze maternal age, association with intercurrences during pregnancy and influence on the determination of childbirth. Method: Observational, retrospective, cross-sectional study with puerperae whose births occurred in 2016, in a hospital in the interior of São Paulo. Results: Of 1130 records analyzed, 22.2% presented